Efisiensi Biaya Produksi terhadap Pendapatan pada Usaha Peternakan Babi di Kecamatan Tareran Kabupaten Minahasa - Sundalangi, Frankie (JBE (Journal of Business and Economics); Volume 2 No.1, 2003 JBE UNKLAB, 2003)
Pig farming efficiency on income cost, that is constrains in farming beside social-economic in others, due to every livestock have the unique problem relation to increase farming income. The matter in research is, what does the effect of cost determinants i.e feed-price, labor-cost and already yet efficiency. The aim of research is analysis the production efficiency of production-cost on peasant’s income in Tareran. For proposed to investigate the efficiency of cost, so using mathematical formulation cited by Gunawan (1995) in Debertin (1986). To follow the model analysis by t-test and degree of freedom (n-3) at α=0,05, summing that partially, each coefficient affected on pig-farming income significant at least 95 percent (α=0,05). F-test result showed that collectively high-significant on pig-farming income on research area. Economically the efficiency showed the value of BFM  and NPM ratio on feed-cost that is 1,772652; BFM and NPM ratio of labor-cost valued 4,861108; BFM and NPM ratio of vaccine and vitamin valued that is 2,366268. These values mean that the applicable feed-price, labor-cost, vaccine and vitamin is not efficient yet, course its value more that one. Study’s conclusion stated that the whole of production-cost is not efficient yet, economically, so that income level was activate is not optimally, due to marginal product value (NPM) is bigger that marginal factor value (BFM).